Do all patients with hematologic malignancies and severe thrombocytopenia need prophylactic platelet transfusions? Background, rationale, and design of a clinical trial (trial of platelet prophylaxis) to assess the effectiveness of prophylactic platelet transfusions. - Stanworth, S; Dyer, C; Choo, L; Bakrania, L; Copplestone, A; Llewelyn, C; Norfolk, D; Powter, G; Littlewood, T; Wood, E; Murphy, M (2010)
Although considerable advances have been made in many aspects of platelet transfusion therapy in the last 30 years, some areas continue to provoke debate, including the use of prophylactic platelet transfusions for the prevention of thrombocytopenic bleeding in patients with bone marrow failure. We have designed a randomized controlled trial to compare prophylactic platelet use with a threshold of a platelet count of 10 x 10(9)/L with no prophylaxis in adult thrombocytopenic patients with hematologic malignancies. The trial question is whether a no-prophylactic policy for the use of platelet transfusions in patients with hematologic malignancies is not inferior to a threshold prophylactic policy at 10 x 10(9)/L, for bleeding at World Health Organization (WHO) grade 2, 3, or 4, up to 30 days from randomization. The primary outcome measure is the proportion of patients who have a significant clinical bleed, defined as WHO grade 2 or higher up to 30 days from randomization. Subsidiary clinical outcome measures include time to first bleed and a descriptive analysis of all severe bleeds. A bleeding assessment form is completed daily for all study subjects until day 30 from randomization. Minor modifications were made to the definitions at WHO grades 1 and 2 for petechiae and duration of nose bleeds, after piloting of the bleeding assessment forms. This study has been designed as a 2-stage randomized trial with an interim analysis planned after a minimum of 100 patients had been randomized and had completed their period of observation. Patients have initially been enrolled through 3 United Kingdom hematology centers. The interim analysis has been completed, and the results have confirmed a final sample size of 600 patients. Recruitment is now being extended to other centers in United Kingdom and Australia. Local research nurses are not blinded to treatment allocation, but a number of measures to reduce risk of assessment bias include repeated education around standard operating procedures, common definitions, and duplication of assessments. The expected completion date for the 5-year study is December 2011.